Battery plug-in electric vehicle concept design : (battery plug in electric car design - suspension, steering and braking systems) - Pannirsilvam, Vinoth. (2012)
The world is getting more and more concerned with the increase in pollution levels and recently there has been an increase in focus on environmentally friendly vehicles. There have been many emerging technologies that are gaining popularity, but by far the most popular is electric vehicles.